Effects of comb-shaped superplasticizers with different charge characteristics on the microstructure and properties of fresh cement pastes. (30th November 2017) - Zhang, Yan-Rong; Cai, Xiao-Pei; Kong, Xiang-Ming; Gao, Liang
Highlights: Effects of polymers on the microstructure and properties of cement pastes were studied. Charge characteristics of the polymers determine the effects in the order of COO −  > SO3 −  > N + . Polymers with more COO − groups exhibit stronger adsorption capacity and retarding effect. Stronger adsorption leads to superior dispersion, lower viscosity and elasticity. Polymers with cationic charges have lower dispersing capability and fluidizing efficiency. Abstract: The impacts of polycarboxylate co-polymers with varied charge characteristics on the microstructure and properties of fresh cement pastes (FCPs) were investigated. Measurements of adsorption of polymers on cement, cement hydration, microstructure, rheological and viscoelastic properties of FCPs were performed to characterize the performance of the co-polymers. Results show that the effects of the co-polymers on the microstructure and properties of FCPs are determined by their charge characteristics, in the order of COO −  > SO3 −  > N + . Polymers with more carboxylate groups exhibit stronger dispersing capability due to their stronger adsorption capability and retardation effects, thereby bringing about superior dispersion of cement particles, lower viscosity and elasticity of FCPs. The dispersing capability and fluidizing efficiency of the co-polymers with cationic charges are evidently lower than those with negative charges, so are their impacts on the microstructure and properties of FCPs.